A Literature Review of University Endowment Funds in the US and Malaysia - Vendy, Vicky; Sucahyati, Diarany; Widodo, Condro; Hardiansyah, In Naka Malik; Shodiq, Moh. Dhirhan Fajar (Future Science, 2023)
This study aims to review the prior studies regarding the University Endowment Funds in the US and Malaysia. This study uses 6 selected articles published during 2016-2022. This study found universities that manage endowment funds in the US have larger assets, and more aggressive investment strategies. Top-performing universities in terms of endowment funds are Harvard, Yale, Stanford, and Princeton University. However, universities in Malaysia tend to manage smaller assets and invest in less risky assets. Top-performing universities in terms of endowment funds are Universiti Malaya, Universiti Kebangsaan Malaysia, and Universiti Teknologi Malaysia.